2011
DOI: 10.1371/journal.pone.0026032
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein J/Clusterin Is a Novel Structural Component of Human Erythrocytes and a Biomarker of Cellular Stress and Senescence

Abstract: BackgroundSecretory Apolipoprotein J/Clusterin (sCLU) is a ubiquitously expressed chaperone that has been functionally implicated in several pathological conditions of increased oxidative injury, including aging. Nevertheless, the biological role of sCLU in red blood cells (RBCs) remained largely unknown. In the current study we identified sCLU as a component of human RBCs and we undertook a detailed analysis of its cellular topology. Moreover, we studied the erythrocytic membrane sCLU content during organisma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 48 publications
1
35
0
Order By: Relevance
“…In fact, pathologic levels of the secreted chaperone clusterin were only measured in low‐UA donors in vivo. Clusterin is a marker of oxidative stress and injury in many cells including RBCs . It is involved in several physiologic processes including apoptosis, inflammation, cellular senescence, membrane vesiculation, and in vivo aging .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, pathologic levels of the secreted chaperone clusterin were only measured in low‐UA donors in vivo. Clusterin is a marker of oxidative stress and injury in many cells including RBCs . It is involved in several physiologic processes including apoptosis, inflammation, cellular senescence, membrane vesiculation, and in vivo aging .…”
Section: Discussionmentioning
confidence: 99%
“…Newer findings adding to these observations have indicated a functional implication of CLU in human erythrocytes in the aged organism, as well as during erythrocyte senescence [47]. Similarly, CLU has been functionally involved in most age-related diseases including cardiovascular and metabolic syndromes, degenerative diseases, inflammation, and cancer [16,28,48].…”
Section: Functional Implication Of Clu In Ageing and Age-related Disementioning
confidence: 99%
“…Storage lesions include alterations to either morphology (shape changes leading from a discoid to a spherocytic phenotype) or functionality (metabolism and oxygen delivery capacity through an increase in oxygen affinity mediated by a rapid fall in 2,3-diphosphoglycerate concentrations [813]). Further lesions occur in stored RBCs which are reversible to some extent, such as potassium leakage to the supernatant and depletion of ATP and DPG stores, while others are not, such as the alteration of lipids and membrane proteins (membrane protein fragmentation and migration to the membrane and/or vesiculation of subsets of structural or antioxidant proteins [9]), which results in more rigid cell structures, increased osmotic fragility, higher haemolytic rates, phosphatidylserine exposure to the outer membrane leaflet, increased vesiculation rate, and reduced oxygen off-loading capacity [812, 14, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…Membrane protein fragmentation [9, 13], storage time-dependent migration of cytosolic proteins to the membrane [9, 14, 15], and increased oxidative stress-related parameters [9, 16] have been also reported to correlate with storage duration. Biochemical studies explicitly suggested that there is considerable room for improvement in the field of RBC biopreservation, especially when considering that the lifespan of RBCs in vivo is approximately 120 days [17].…”
Section: Introductionmentioning
confidence: 99%